2019
DOI: 10.1002/acm2.12611
|View full text |Cite
|
Sign up to set email alerts
|

Optical surface guidance for submillimeter monitoring of patient position during frameless stereotactic radiotherapy

Abstract: Purpose To evaluate the accuracy of monitoring intrafraction motion during stereotactic radiotherapy with the optical surface monitoring system. Prior studies showing a false increase in the magnitude of translational offsets at non‐coplanar couch positions prompted the vendor to implement software changes. This study evaluated two software improvements intended to address false offsets. Methods The vendor implemented two software improvements: a volumetric (ACO) rather than planar calibration and, approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 23 publications
3
41
0
Order By: Relevance
“…Similar to a previous study, RTDs at non‐zero couch angles were larger than RTDs observed at the end of treatment, indicating SI system performance is still sub‐optimal at non‐zero couch angles. Additionally, the largest component of the translation magnitude continues to be from offsets reported in the longitudinal direction as shown in Table 2 Minimal offsets in the vertical direction are also consistent with previously reported aggregate data 16 . Larger RTDs were noted on the 270° side of the treatment couch suggesting differences that may be attributed to camera pod geometry or an individual camera's performance.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similar to a previous study, RTDs at non‐zero couch angles were larger than RTDs observed at the end of treatment, indicating SI system performance is still sub‐optimal at non‐zero couch angles. Additionally, the largest component of the translation magnitude continues to be from offsets reported in the longitudinal direction as shown in Table 2 Minimal offsets in the vertical direction are also consistent with previously reported aggregate data 16 . Larger RTDs were noted on the 270° side of the treatment couch suggesting differences that may be attributed to camera pod geometry or an individual camera's performance.…”
Section: Discussionsupporting
confidence: 87%
“…This choice sets the exposure times of the cameras and are aimed to improve the variations that can affect the performance of RTDs due to skin tone. Darker skin tones will absorb more Minimal offsets in the vertical direction are also consistent with previously reported aggregate data 16. Larger RTDs were noted on the 270°side of the treatment couch suggesting differences that may be attributed to camera pod geometry or an individual camera's performance.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…For treatments with non-coplanar couch angles, accurate knowledge about the coincidence between radiation and couch rotation isocenter becomes important, as it is not possible to correct for couch walkout during treatment delivery. Regular Winston-Lutz checks provide accurate information about the radiation isocenter for different gantry, collimator and couch angles and can also indirectly provide information about the accuracy of the system [ 19 , 54 , 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…Optical Surface Tracking (OST) seems to be a sophisticated and suitable option, as it intends to reduce set-up errors and provides real-time non-invasive monitoring to detect patient movement during treatment, without the use of ionizing radiation. [24][25][26] The aim in this work is to demonstrate how a commercial OST system can be implemented to monitor patient positioning during treatment for a non-coplanar single isocenter VMAT technique for multiple BM and to show the feasibility of this system by defining treatment tolerances without compromising the treatment margins.…”
Section: Introductionmentioning
confidence: 99%